Some results on biorthogonal polynomials - Richard W. Ruedemann (International Journal of Mathematics and Mathematical Sciences)
Some biorthogonal polynomials of Hahn and Pastro are derived using a polynomial modification of the Lebesgue measure dθ combined with analytic continuation. A result is given for changing the measures of biorthogonal polynomials on the unit circle by the multiplication of their measures by certain Laurent polynomials.